2013
DOI: 10.1093/pasj/65.2.38
|View full text |Cite
|
Sign up to set email alerts
|

Phase Variation of Earthshine Polarization Spectra

Abstract: We present the results of the optical spectropolarimetry of Earthshine on the Moon for Earth phase angles ranging from 49 • to 96 • . The observations were conducted on 2011 March 9-13 (UT) using the spectropolarimeter HBS installed on the 1.88 m telescope at Okayama Astrophysical Observatory. The wavelength coverage was 450-850 nm with a resolution of 6 nm. The observed Earthshine polarization degree spectra exhibit decreasing polarization degree with increasing wavelength at any phase. The overall degree of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 37 publications
2
42
0
Order By: Relevance
“…Various groups (Dollfus 1957;Wolstencroft & Breon 2005;Sterzik et al 2012;Takahashi et al 2013;Bazzon et al 2013) have reported a similar property. In our data, we observe that the linear polarization intensity remains nearly constant at about 5.7% between ∼0.8 μm and 0.9 μm.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Various groups (Dollfus 1957;Wolstencroft & Breon 2005;Sterzik et al 2012;Takahashi et al 2013;Bazzon et al 2013) have reported a similar property. In our data, we observe that the linear polarization intensity remains nearly constant at about 5.7% between ∼0.8 μm and 0.9 μm.…”
Section: Resultsmentioning
confidence: 87%
“…This can be done by observing the earthshine, which is the sunlight scattered by the dayside Earth and reflected by the nightside of the Moon. The optical and near-infrared earthshine spectra reveal atmospheric and surface biosignatures and are sensitive to features like water clouds, oceans, deserts, and volcanic activity (e.g., Woolf et al 2002;Turnbull et al 2006;Montañés-Rodríguez et al 2006;Pallé et al 2009;García Muñoz et al 2012); many are present in the earthshine optical spectropolarimetric data (Sterzik et al 2012;Takahashi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Another spectra-polarimetric observation of the earthshine was published by Takahashi et al (2013). They also find a rise in the fractional polarization of the earthshine toward the blue but with a much flatter slope.…”
Section: Comparison With Previous Measurementsmentioning
confidence: 90%
“…Therefore, only a qualitative comparison with our data can be made. The observations of Takahashi et al (2013) are conducted on five consecutive nights and cover phase angles α = 49…”
Section: Comparison With Previous Measurementsmentioning
confidence: 99%
“…The size of the disk integrated rainbow polarisation signal for the Earth has not been measured, but in principle could be obtained from lunar earthshine polarisation measurements. Current data however does not have sufficient phase coverage (Sterzik, Bagnulo, & Palle 2012;Takahashi et al 2013;Bazzon, Schmidt, & Gisler 2013).…”
Section: Signatures Of Habitabilitymentioning
confidence: 99%